A Birthday for Bear - Becker, Bonny; Denton, Kady MacDonald (Somerville, Mass. : Candlewick Press, 2009)
Despite Bear's efforts to ignore his birthday, Mouse will not rest until his friend celebrates.
A Junior Library Guild selection
Keywords: Birthdays -- Fiction; Bears -- Fiction; Mice -- Fiction; Friendship -- Fiction